An Analytical Study: The Great Umayyad Mosque in Damascus: Through the Journeys of Ibn Jubayr and Ibn Battuta: As a Model (London Journal of Research In Humanities and Social Sciences, 2026)
This article is about the Great Umayyad Mosque in Damascus through the journeys of the Andalusian traveler Ibn Jubayr (d. 1217 AD) called: “Rihlat Ibn Jubayr- Travels of Ibn Jubayr” or what is called: “Taḏkira bi-akhbār can ittifāqāt al-asfār- A Reminder of News about Travel Agreements”, and the Moroccan traveler Ibn Battuta (d. 1377 AD) called: “Tuhfaf An-Nuzzar fi Ghara’ib al-Amsar wa-‘Aja’ib Al-Asfar- A masterpiece for the observer of the wonders of countries and the wonders of travel ” – as a model, as these two journeys, despite the time distance between them, are the truest mirror of the era in which their author lived, as what they wrote of literary texts, stories and news is an important source of information about the city of Damascus in the Middle Ages, and what it contains of monuments and religious architecture, the most important of which is the Great Umayyad Mosque.
Keywords: Damascus; Great Umayyad Mosque; Ibn Battuta; Ibn Jubayr; Islamic Architecture; Medieval Travel Literature; Religious Heritage; Umayyad Period